Effects of Tungsten Bur and Flame with Sandblasting Reconditioning Methods on Friction Resistance and Gate Patency of Different Self-Ligating Brackets: An In Vitro Study - Noor L. Aftan; Dheaa H. Al-Groosh (Dental Hypotheses)
Introduction: This study aimed to evaluate and compare the effects of tungsten bur and flame with sandblasting (FS) reconditioning methods on gate patency and frictional resistance of different self-ligating brackets. Methods: A total of 260 stainless steel self-ligating brackets of 4 brands (2 passive and 2 interactive), with a 0.022-inch slot size, were used. Two bracket reconditioning methods were used: the tungsten bur and FS. The gate opening and closing forces and frictional resistance of the brackets were assessed using a universal testing machine. Results: Reconditioning methods had no statistically significant effect on static and kinetic friction among all types of brackets (P > 0.05). Similarly, reconditioning methods had no statistically significant effect on the opening forces of the Lotus Plus bracket or the closing forces of the Direct-to-Consumer (DTC) and IOS bracket (P > 0.05). However, all other variables showed statistically significant differences (P < 0.05). Conclusion: The frictional resistance of the brackets was not significantly affected by reconditioning, whereas gate patency was affected differently between brands, especially with the FS reconditioning method.